Repurposing nicardipine leads to improved development in a young patient with Pitt–Hopkins syndrome - Somorai, Marta Agnes; Ekins, Sean; Rupprecht, Claudia; Lettl, Clara; Mall, Volker (Frontiers in Pharmacology, 2025)
We describe a drug repurposing treatment involving the use of nicardipine in a young patient with Pitt-Hopkins syndrome (a rare neurodevelopmental disorder that results from variants of TCF4 gene) as a bench-to-bedside approach. Loss of TCF4 function in Pitt–Hopkins syndrome leads to increased excitability of Nav1.8 in neurons. Nicardipine is normally used alone or together with other medicines to treat severe chest pain (angina) or high blood pressure (hypertension), and can also be used in children to treat hypertension. Nicardipine was shown to have an inhibitory effect on Nav1.8 in vitro as well as in Tcf4+/− mice, showing promising effects on behavior, learning and memory. In this study, nicardipine was given orally for 7 months (starting dose 0.2 mg/kg/d, maximum dose 1.7 mg/kg/d). There were no significant side effects. The patient showed mild to moderate improvement in all developmental trajectories as well as in her restlessness. Repurposing nicardipine in Pitt-Hopkins syndrome patients could be a promising approach to enhance development in these often severely affected patients.